RHEUMATIC FINDINGS IN MAJOR AND INTERMEDIATE BETA-THALASSEMIA - ARMAN, MI; BEKTAS, S (Springer Heidelberg, 1989)
Muscoskeletal systems of 19 patients with major and intermediate beta thalassemia were evaluated clinically and radiologically. Rheumatic findings were determined in 17 patients. Symptoms were localized mainly at shoulders, knees, and ankles. The most frequent signs were pain, inflammation, crepitance, radiologically determined periarticular cystic formations, and osteoporosis. Joint involvement was in the nature of non-erosive, destructive osteoarthropathy. It was also found that the symptoms in males were more severe and numerous than in females. No difference was observed between major and intermediate thalassemia cases. There was no correlation between the therapy and the findings. Upper limb involvement was almost equal to the lower limb involvement in contrast to a previous study.